The Effect Of Sales And Operating Costs On Net Profit At Pt Forisa Nusapersada Tangerang - Nurjanah, Dede; Ramadhani, Fadillah Dwi Suci (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Forisa Nusapersada is a company engaged in the production and marketing of various beverages and foods, especially in high-quality powdered form. PT. Forisa has quite high sales and also has significant operational costs to support the sales and marketing of the company's products. However, do PT. Forisa Nusapersada's sales and operational costs significantly affect the company's net profit? High sales or revenue with low operational costs will result in a good profit for the company. High sales do not necessarily result in a goodnetprofit when operational costs are also high, low sales do not necessarily result in a loss if accompanied by low operational costs, and high sales if met with high operational expenses that even exceed revenue, what happens to the company is a loss. Operating costs significantly affect a company's profit results, because the higher the costs incurred, the lower the profit obtained by the company. This study aims to delve deeper into the relationship and significance of the influence of these two variables on the company's profitability, thereby providing a clear picture of the strategies that need to be optimized to achieve solid financial performance. The research uses a quantitative approach with a descriptive and associative design, utilizing three years of financial data (2021-2023). Data collection was done through documentation and literature review. The sample size is extremely small N=3) which leads to perfect multicollinearity and invalid statistical inference. The results show sales have a positive effect, while operating costs have a negative effect on net profit. All three variables exhibit a perfect linear relationship due to the small sample size and high multicollinearity VIF = 3406.832), invalidating the regression analysis for generalization.